A test of the stability of punishment hypothesis: The Dutch case - Fiselier, Jan P. S. (Journal of quantitative criminology, 1992)
This paper tests the hypothesis of the stability of punishment as developed by Blumstein and his associates against Dutch prison data. After summarizing the existing empirical evidence, Dutch prison data are presented pertaining to the average daily population in penal institutions, on the one hand, and the number of admissions in these institutions, on the other hand. In three ways it is tested whether these data do support the hypothesis: regression analysis, Box-Jenkins analysis, and the analysis of a few dynamic models as presented by Berk et al. (1981). The paper ends with discussing Blumstein's hypothesis and considers the way research into the extent of the prison population should be continued.